Two New Species of Ochlandra Thw. (Poaceae - Bambusoideae) from Southern India - Kumar, Muktesh; Seethalakshmi, K. K.; Sequiera, Stephen (Rheedea, 1999)
Two new species of Ochlandra Thw. are described from Kerala State, India.